2020
DOI: 10.1038/s41467-020-16873-7
|View full text |Cite
|
Sign up to set email alerts
|

Regular-triangle trimer and charge order preserving the Anderson condition in the pyrochlore structure of CsW2O6

Abstract: Since the discovery of the Verwey transition in magnetite, transition metal compounds with pyrochlore structures have been intensively studied as a platform for realizing remarkable electronic phase transitions. We report on a phase transition that preserves the cubic symmetry of the β-pyrochlore oxide CsW2O6, where each of W 5d electrons are confined in regular-triangle W3 trimers. This trimer formation represents the self-organization of 5d electrons, which can be resolved into a charge order satisfying the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…Still, the evaluated energy splitting of E 1 − E 2 ∼0.2eV is as large as the bandwidth of our system (see Appendix A), which is compatible with the first principles band structure given in Ref. [33] where we roughly evaluate t ∼ 0.06 eV by their bandwidth.…”
Section: Summary and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Still, the evaluated energy splitting of E 1 − E 2 ∼0.2eV is as large as the bandwidth of our system (see Appendix A), which is compatible with the first principles band structure given in Ref. [33] where we roughly evaluate t ∼ 0.06 eV by their bandwidth.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…The SOC-induced flat band clarifies the origin of the trimerized charge ordering observed in CsW 2 O 6 33 . Figure 1(d) shows the mean field phase diagram at quarterfilling, corresponding to two electrons per tetrahedron.…”
Section: A Phase Diagrammentioning
confidence: 58%
See 2 more Smart Citations
“…Structural symmetry breaking caused by the ordering of electronic multiple degrees of freedom coupled to the lattice, occurs ubiquitously in transition metal compounds [1][2][3]. Examples include iron chalcogenides/pnictides superconductors [4][5][6] and materials forming exotic low-temperature orbital molecules [7][8][9][10][11][12][13][14][15][16][17][18]. Recently, it was found that symmetry breaking can occur locally, as a precursor, even above the transition temperature [18][19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%